Plasma and whole blood mefloquine concentrations during treatment of chloroquine-resistant falciparum malaria with the combination mefloquine-sulphadoxine-pyrimethamine. - Karbwang, J; Looareesuwan, S; Phillips, R; Wattanagoon, Y; Molyneux, M; Nagachinta, B; Back, D; Warrell, D (1987)
Mefloquine-sulphadoxine-pyrimethamine (MSP) in combination has proved effective against multiple-drug-resistant falciparum malaria, but nothing is known about mefloquine absorption when it is given in this formulation. Nine Thai patients, aged 15-51 years with uncomplicated chloroquine-resistant falciparum malaria, took 11.2-16.7 mg of mefloquine base per kilogram bodyweight as MSP tablets. All patients responded to treatment with fever and parasite clearance times of 61 +/- 29 h (mean +/- s.d.) and 52 +/- 24 h, respectively. The mean apparent absorption half-time (t1/2abs) of mefloquine was 4.89 h (range 2.25-9.72) and mean peak plasma concentration was 1815 ng ml-1 (range 725-3368). Peak plasma mefloquine concentrations in three patients who vomited within 2 h of treatment were 725, 956 and 1972 ng ml-1. There was no significant difference between plasma and whole blood mefloquine concentrations during the first 48 h of treatment. Based on the elimination of parasitaemia, the plasma mefloquine concentrations are adequate for therapy of uncomplicated falciparum malaria although the relationship between plasma concentrations and therapeutic efficacy of mefloquine requires further study.